Soft Supracrystals of Au Nanocrystals with Tunable Mechanical Properties. (9th January 2013) - Yan, Cong; Arfaoui, Imad; Goubet, Nicolas; Pileni, Marie‐Paule
Abstract The elastic properties of highly ordered three‐dimensional colloidal crystals of gold nanocrystals (called supracrystals) are reported. This study is based on the simultaneous growth of two kinds of gold nanocrystal supracrystals that range in size from 5 nm to 8 nm: interfacial supracrystals and precipitated supracrystals. The elastic properties are deduced from nanoindentation measurements performed with an atomic force microscope. The Young's modulus of the interfacial supracrystals, which grow layer‐by‐layer and form well‐defined films, is compared to that of precipitated supracrystals, which are produced by homogeneous growth in solution. For the precipitated supracrystals, characterized by a thickness larger than 1 μm, the Oliver and Pharr model is used to determine the elastic moduli, which are in the gigapascal range and decrease with increasing nanocrystal size. For the interfacial supracrystals, with 300 nm average thickness, a second model (plate model) is applied in addition to the Oliver and Pharr model. These two models confirm independently that the interfacial films are very soft with Young's modulus in the range of 80–240 MPa. This result reveals a totally new feature of nanocrystal solids, never emphasized before. It is shown that these changes in the Young's modulus are related to the supracrystal growth mechanism.